Integrating behavioral assessment in instructional design for competency-based medical education - Williams, K. N.; Lazzara, Elizabeth H.; Sadighi, M.; Chandran, N.; Joshi, K.; Raj, S.; Shields, I.; Nichols, B.; Testa, D.; Hernandez, J.; Michael, M.; Rege, R.; et al. (Frontiers in Medicine, 2024)
As institutions continuously strive to align with the standards set forth within competency-based medical education, there is an increased need to produce evidence of learner achievement in the form of observable behaviors. However, the complexity of healthcare education and clinical environments make it challenging to generate valid and reliable behavioral assessments. In this article, we utilize our interdisciplinary knowledge from the perspectives of experts in medical education, assessment, and academic administration to provide tips to successfully incorporate behavioral assessments into instructional designs. These include tips for identifying the best assessment methods fit for purpose, guiding instructors in establishing boundaries of assessment, managing instructors, selecting raters, generating behavioral assessment guides, training raters, ensuring logistics support assessment strategies, and fostering capacity for iteration. These can be used by institutions to improve planning and implementation for longitudinal behavioral assessments.